Immigration and Crime in Canadian Cities: A 35-Year Study - Jung, Maria (Canadian journal of criminology and criminal justice, 2020)
This study examines whether changes in immigration are associated with changes in crime rates in Canadian census metropolitan areas for the period 1976-2011. Using data from the Uniform Crime Reports and the Canadian census, this study employs fixed effects regression models to analyse the changes in immigration and crime rates during this 35-year period. Controlling for changes in demographic and socio-economic co-variates, overall changes in the proportion of the population that is foreign-born are either not significantly associated or negatively associated with changes in crime rates within Canadian cities. Overall, this article adds to the literature by using a longitudinal design within a Canadian urban context, employing multiple measures of immigration, and extending the analysis beyond one type of crime. (English)